Effect of Oxygen on Verbenone Conversion From cis-Verbenol by Gut Facultative Anaerobes of Dendroctonus valens - Cao, Qingjie; Wickham, Jacob D.; Chen, Li; Ahmad, Faheem; Lu, Min; Sun, Jianghua (Frontiers in Microbiology, 2018)
Since its introduction from North America, Dendroctonus valens LeConte has become a destructive forest pest in China. Although gut aerobic bacteria have been investigated and some are implicated in beetle pheromone production, little is known about the abundance and significance of facultative anaerobic bacteria in beetle gut, especially with regards to effects of oxygen on their role in pheromone production. In this study, we isolated and identified gut bacteria of D. valens adults in an anaerobic environment, and further compared their ability to convert cis-verbenol into verbenone (a multi-functional pheromone of D. valens) under different O2 concentrations. Pantoea conspicua, Enterobacter xiangfangensis, Staphylococcus warneri were the most frequently isolated species among the total of 10 species identified from beetle gut in anaerobic conditions. Among all isolated species, nine were capable of cis-verbenol to verbenone conversion, and the conversion efficiency increased with increased oxygen concentration. This O2-mediated conversion of cis-verbenol to verbenone suggests that gut facultative anaerobes of D. valens might play an important role in the frass, where there is higher exposure to oxygen, hence the higher verbenone production. This claim is further supported by distinctly differential oxygen concentrations between gut and frass of D. valens females.